Methods of teaching and evaluation of learning outcomes in the discipline «Pedagogical skills» (Journal of Educational Sciences, 2022)
In this article, the authors reveal the content of pedagogical skill, its elements. The authors pay special attention to the formation of pedagogical skills among future teachers based on modern technologies, methods of teaching, and upbringing, which can be considered an ideal of pedagogical activity thatencourages teachers to self-improvement and a standard that includes an assessment of the effectivenessof pedagogical work.Pedagogical excellence implies such professional qualities that take into account and recognize theindividuality, uniqueness of the student’s personality, allow him to build the process of education andupbringing in such a way as to provide students with the maximum favorable conditions for revealingtheir creative potential, creativity and the best characterological features of the individual.Pedagogical skills of teachers, expressed in a combination of individual human and professionalqualities, love for their work – conditions for the formation of the personality of a future specialist. Thecomponents of pedagogical skills are considered considering the individual approach of action, the formation of the main structures of the teacher’s personality, and methods of pedagogical influence.Implementing current education policies is impossible without a teacher with high professionalism, creative potential, and leading academic positions in society. A modern teacher, working with theintellectual saturation of the content of Education, a high level of teaching methods, strives to know,love, and help university students to create themselves, thinks about the degree of participation in themodernization and development of the University.The pedagogical activity contributes to the implementation of social continuity of generations, including young people in the system of social contacts. It helps to realize the natural capabilities of aperson in mastering social experience.Key words: Pedagogical skills, pedagogical techniques, pedagogical competence, learning achievements, tools for assessment and measurement, nanotechnology.